Autotrophic and heterotrophic contributions to short-term soil CO 2 efflux following simulated summer precipitation pulses in a Mediterranean dehesa - Casals, Pere; Lopez-Sangil, Luis; Carrara, Arnaud; Gimeno, Cristina; Nogués, Salvador (Global Biogeochemical Cycles, 2011)
Autotrophic and heterotrophic components of soil CO2 efflux may have differential responses to environmental factors, so estimating the relative contribution of each component during summer precipitation pulses is essential to predict C balance in soils experiencing regular drought conditions. As even small summer rains induced high instantaneous soil respiration rates in Mediterranean wooded grasslands, we hypothesized that standing dead mass, surface litter, and topsoil layer could play a dominant role in the initial flush of CO2 produced immediately after soil rewetting; in contrast, soil CO2 effluxes during drought periods should be mostly derived from tree root activity. In a grazed dehesa, we simulated four summer rain events and measured soil CO2 efflux discontinuously, estimating its d 13 C through a Keeling plot nonsteady state static chamber approach. In addition, we estimated litter contribution to soil CO2 efflux and extracted soil available C fractions (K2SO4‐extracted C and chloroform‐fumigated extracted C). The d 13 C‐CO2 from in‐tube incubated excised tree roots and rewetted root‐free soil was −25.0‰ (±0.2) and −28.4‰ (±0.2), respectively. Assuming those values as end‐members’ sources, the autotrophic component of soil CO2 efflux was dominant during the severe drought, whereas the heterotrophic contribution dominated from the very beginning of precipitation pulses. As standing dead mass and fresh litter contribution was low (<25%) in the first day and negligible after, we concluded that CO2 efflux after rewetting was mostly derived from microbial mineralization of available soil organic C fractions.
Keywords: d13C; Drought; precipitation manipulation (voyant); Soil CO2 efflux